The influence of a preworkout energy drink (C4) on lower limb neuromuscular activation in healthy young adults - Rosario, Martin G; Parks, Kaci; Rountree, Garett; Torre, Joe De La (Journal of Sports Research, 2023)
Energy drinks (Edrinks) have a plethora of ingredients for the same objective, a burst of energy and improving mood among others. However, there are various Edrink brands with diverse ingredients and slightly different purposes, such as the C4 drink which is a pre-workout. This ingredient variation can provoke different neuromuscular balance and gait adaptations. Recent studies suggest that some ingredients in Edrinks can aid in muscle fatigue in lower limb musculature. To investigate the lower limb neuromuscular modification after edink (C4) consumption. Ten participants (1 male and 9 females) partaken in the study (age of 23.4 (+/- 2.95). Neuromuscular activation of leg musculature was measured during a single-legged balance test on a firm and foam surface, pre and post edrink. Balance tests were designed to engage diverse areas of the balance systems (visual, proprioceptive and vestibular) while studying the adaptations in lower limb muscles such as tibialis anterior and gastrocnemius. The main outcome of this study showed a trend towards greater onset, faster TP, and slower decay for leg muscles after edrink consumption. It seems C4 beverage provokes a faster and prolonged recruitment of the leg muscles. Future studies should look into the postural adaptations after the said drink.